Aplikasi Pendukung Pengambilan Keputusan Siswa Yang Berhak Mendapatkan Beasiswa Berbasis Web Menggunakan Metode Fuzzy - Muhammad Rizaldy Pratama; Ari Syaripudin (CV. Multi Kreasi Media, 2023)
At the moment, technology has advanced quickly throughout many industries, including education. Many processes in the sphere of education continue to be manual and unaided by technology, such as the calculation and reporting of scholarships, which is still done by hand without the use of a system or application. The study's focus was at the YAPIA Pondok Aren Vocational High School. Because of this, a decision-making assistance tool is required to decide which students, using the fuzzy method, are eligible for a website-based scholarship. Using the Tsukamoto fuzzy model, this system can help identify students who fit the requirements for scholarships depending on predefined criteria. Decision support systems (DSS) are used as a tool for decision makers to expand the capabilities of decision makers, but not to replace the evaluation of decision makers.